Development and Evaluation of Hesperidin-loaded Ethosomal Gel for Wound Healing (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Wound healing is a process that restores and regenerates the injured tissues. Polyphenols(Hesperidin) show wound healing properties, but their effective topical application for skin wound healing ischallenging due to issues with low loading capacity and delivery efficiency. Ethosomes (lipid-based vesicles)have overcome such problems and emerged as a promising delivery system for improving drug encapsulation andpenetration through the skin. Materials and Methods: Hesperidin-loaded ethosomes were formulated with 30%ethanol and analyzed for particle size and shape, encapsulation efficiency, and surface charge. Ethosomes gel wasthen formulated with 1% w/v Carbopol 934K. Further Hesperidin-loaded ethosomal gel was evaluated for variousparameters such as organoleptic properties, pH, viscosity, and skin permeation. An in-vitro wound healing assaywas performed to assess the angiogenic properties of Hesperidin-loaded ethosomal gel along with its comparisonwith pure Hesperidin. Results: The formulated ethosomes were found to have a spherical shape, a vesicle size of417.9 nm, an entrapment efficiency of 87.32%, and a surface charge of −26.62 mV. The ethosomal gel showedan optimal pH of 5.7, good spreadability, and a release of 86.21%. It has shown stability over 60 days. In-vitroassay revealed that both Hesperidin-loaded ethosomal gel and powder exhibited angiogenic effects, significantlypromoting angiogenesis in HaCaT cells over time. Conclusion: The development of Hesperidin-loaded ethosomalgel has successive delivery and addressed the challenges of high loading capacity and effective skin permeation.The results suggest that Hesperidin-loaded ethosomal gel is an effective method for enhancing wound healingthrough improved delivery.